1994
DOI: 10.2307/3578689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radiation and Age on Immunoglobulin Levels in Rhesus Monkeys (Macaca mulatta)

Abstract: We report the results of a study on the immunoglobulin levels of rhesus monkeys (Macaca mulatta) in a colony consisting of the survivors of monkeys that received a single whole-body exposure to protons, electrons or X rays between 1964 and 1969. This colony has been maintained to assess the long-term effects of ionizing radiation on astronauts and high-flying pilots. Of the original 358 monkeys that were retained for lifetime studies, 129 (97 irradiated and 32 controls) were available for our study. We found n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Further decrements were evident in the oldest animals assessed in the second study, and many old monkeys should be categorized as non-responders. The poor vaccine response is not due to low antibody production in general, because overall immunoglobulin in circulation, especially IgA, tends to rise slightly in older monkeys (Stone et al 1994). In part, the inadequate responses were due to our focus on primary immunizations, and the absence of prior influenza infections in modern animal facilities following BSL-2 practices and using protective garb.…”
Section: Discussionmentioning
confidence: 97%
“…Further decrements were evident in the oldest animals assessed in the second study, and many old monkeys should be categorized as non-responders. The poor vaccine response is not due to low antibody production in general, because overall immunoglobulin in circulation, especially IgA, tends to rise slightly in older monkeys (Stone et al 1994). In part, the inadequate responses were due to our focus on primary immunizations, and the absence of prior influenza infections in modern animal facilities following BSL-2 practices and using protective garb.…”
Section: Discussionmentioning
confidence: 97%
“…For example, among atomic bomb survivors in Hiroshima and Nagasaki disturbed antibody production might last for a long time, the IgA and IgM in them still expressed at high level ~6) after decades of years. A long-term experiment study conducted in Air-Force Biological Center, USA showed that there was no significant difference of immunoglobulin levels between the survivals of radiated monkeys and the control, but those non-survivor (died from infection and tumor) showed obvious immunosuppression (7) . The monocytes-macrophage system constitutes the first line of defense resisting the exogenous noxious factors, which takes responsibility for processing and presenting the special antigen, participates directly in antigen recognition, activating immunocytes to produce antibody.…”
Section: Characteristics Of Radiation Damage In Immune Systemmentioning
confidence: 99%